Collective memory and social imaginaries of the epidemic situation in COVID-19—based on the qualitative research of college students in Wuhan, China - Luo, Renqi; Feng, Weiyi; Xu, Yuan (Frontiers in Psychology, 2022)
This study conducted in-depth interviews with 20 students from a university in Wuhan so as to obtain data regarding their collective memory at the early stage of the COVID-19 outbreak and their social imaginaries in the longitudinal dimension of time. Compared with those in other regions, interviewees from Wuhan show more fear and dissatisfaction and think that others find it difficult to empathize with their first-hand experiences. Interviewees from Wuhan are more dependent on the media. However, media use can cause problems related to redundant information and emotional impact. While one is confined to home, he/she is forced to participate in communication with family members and the topic of the body is discussed again from a new angle. Trauma leads to self-reconciliation, as facilitated by the re-examination of and reflection on one’ nomination of and reflection on n family members and the months in the wake of the COVID-19 outbreak. However, having received a collectivist education since childhood and having been guided by the discourse system created by the state media, they have since been able to shape their sense of identity and strengthen their sense of national honor.